Mouse noses on toast - King, Daren, 1972-; Roberts, David, 1970- (London : Faber and Faber, 2008)
Paul Mouse gathers a group of mouse activists to uncover the mystery behind the delicacy known as "Mouse noses on toast" which is served in a fancy human restaurant.
Keywords: Food habits -- Fiction; Mice -- Fiction; Mystery and detective stories